VALIDASI METODE PENETAPAN KADAR VITAMIN C EKSTRAK DAUN KEMANGI (Ocimum sanctum L.) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Kurniawati, Evi; Lestari, Tri Puji (Jurnal Insan Farmasi Indonesia, 2024)
Basil leaves (Ocimum sanctum L.) are a type of wild plant that easy to find. Basil is known to be analgesic, antihyperlipid and has antioxidant properties. Besides, basil is also known to treat stomach and liver diseases. Components known to be found in basil plants include flavonoids, alkaloids, saponins, triterpenoids, steroids, tannins, phenols and vitamin C, that is needed by a person to be able to carry out metabolism properly and develop normally. The aim of the research to validate the determination of vitamin C levels from basil leaf extract. The basil leaf filtrate was identified for vitamin C by a color reaction and then the levels were determined by UV-Vis spectrophotometry which was previously validated with the parameters of accuracy, precision, linearity and selectivity. According to the research results, it is known that the accuracy test meets the percent recovery range in the range of 98-102%, the precision test produces an RSD of less than 2%, the linearity test produces a correlation value (r) = 0.9986 and the selectivity test is good. The method for determining vitamin C levels by Uv-Vis spectrophotometry was validated on parameters that met the requirements of 0.0128% w/w.